Seroprevalence and altitude-dependent patterns of Toxoplasma gondii infection in livestock from northern Armenia - Ruzanna Gevorgyan; Sargis A. Aghayan; Oleg Shcherbakov; Ahmad Daryani; Tigran Abgaryan; Hasmik Gevorgyan (PLoS ONE, 2026)
Toxoplasmosis, caused by the intracellular protozoan parasite Toxoplasma gondii , is a zoonotic disease affecting almost all warm-blooded vertebrates. Despite its importance to both humans and animals, research on toxoplasmosis in Armenia has been limited, with a notable 35-year gap in studies focused on host animals. This study aimed to conduct a survey of T. gondii seroprevalence among livestock in Armenia. A total of 1996 serum samples of sheep, pigs, and cattle were collected from the northern provinces (Shirak, Lori, Tavush) of Armenia and screened by the ELISA test for the presence of total anti- Toxoplasma IgG and IgM antibodies. In the present study, the overall seroprevalence of T. gondii in livestock from northern Armenia was 15.5% (308/1,982; 95% CI: 14.0–17.2). The overall prevalence of infection among sheep was 22.5% (196/870; 95% CI: 19.8–25.5), pigs 28.6% (4/14; 95% CI: 8.4–58.1), and cattle 10.1% (112/1,112; 95% CI: 8.4–12.0). After excluding pigs due to insufficient sample size, a Pearson’s chi-square test demonstrated a strong and statistically significant association between host species and T. gondii infection status (χ² = 58.31, df = 1, p < 0.001). To investigate environmental determinants of infection, species-specific logistic regression models were fitted using temperature and elevation as continuous predictors. In cattle, none of the environmental variables showed statistically significant associations with seropositivity, and model fit did not improve over the null model. In contrast, sheep displayed a strong and non-linear relationship between seropositivity and elevation. The likelihood of infection decreased from low to mid altitudes and rose slightly at the highest elevations. Temperature showed no detectable effect in either species. These findings reveal clear species-specific differences in environmental sensitivity and highlight elevation as a key ecological factor shaping T. gondii exposure risks in sheep.